Analisis Perbedaan Kadar Lemak, Total Padatan dan Kecepatan Leleh Es Krim Buah Naga Merah (Hylocereus Polyrhizus) dari Bahan Krimmer yang Berbeda - Fadhila, Jihan; Kurnia, Pramudya; Sofyan, Aan (Universitas Tadulako, 2025)
Ice cream quality is determined by the fat content, total salids and melting speed which mutally affect the texture, softness and stability of the product. Fat acts as a texture former and air stabilizer, while high total solids can improve the structure and slow down the melting process. The use of vegetable creamer based on dietary fiber such as inulin can maintein the viscosity and stability of the emulsion without increasing the fat content significantly. The cremaer ingredients used in this study were fiber crème, coconut milk and UHT (Ultra High Temperature) milk as a control. The purpose of this study was to copare the composition of differences in fat content, total solids and melting speed of ice cream from different main ingredients. This study is an experimental study using a Completely Randomized Design (CRD) with 3 formulas and 2 replications. The average results of the fat content analysis in coconut milk (6.32%), UHT milk (2.53%) and fiber crème (8.74%). The average results pf total solids analysis in coconut milk (54.76%), UHT milk (53.63%) and fiber crème (54.57%). The results of the analysis on the melting speed of ice cream melted perfectly for 30 minutes. The fat content was analyzed using the Mojonnier modification method, showing that the highest fat content was found in fiber crème with a value that had met the Indonesian National Standard (SNI) namely the minimum limit of 5% with the resultd of the analysis p = 0.018 incadicating a difference in a fat content in the creamer variants. The resultd of total solids and melting speed of dragon fruit ice cream showed a p value >0.05, which means there was no sinificant difference between the variations in the use of creamer ingredients. The conlusion of the ingredients for fat content, total slids and melting speed of ice cream that meets SNI standards is fiber crème.